Transformation of Event Trends in the Context of Socio-Cultural Development of Ukraine - Liudmyla Polishchuk (Socio-Cultural Management Journal)
Introduction. The modern event sphere is highly dynamic and adaptive; it responds quickly to current challenges and external circumstances, forming new trends and determining development trends. Despite the losses and crises caused by the pandemic and exacerbated by the war, the event market in Ukraine continues to develop and become more competitive. Knowledge and understanding of trends allow professionals to create innovative formats and unique offers, adapt international experience to domestic realities, and be flexible and progressive. At the same time, today’s domestic events reflect and shape the new values of Ukrainian society – charity, volunteering, inclusiveness, and national identity. Global trends related to the use of digital technologies, data analytics, mobile applications, gamification, etc., are integrated into domestic events, combining traditions and innovative approaches. Purpose and methods. The article aims to analyse the transformation of event trends in the 2020s of the twenty-first century, identify the relationship with socio-cultural, social, political, economic, and other factors of the development of Ukrainian society, and outline prospects for further research. The study used methods of analysis and synthesis, which made it possible to analyse event trends as a separate phenomenon and, in combination with external factors, identify their impact on the socio-cultural development of Ukraine. The comparison method allowed for the identification of differences in technologies, formats, and methods inherent in events of different years. Results. Modern event trends have been systematised, focusing on forming new trends in the event sector under the influence of external circumstances, such as the improvement of digital tools, diversification of technologies, the COVID-19 pandemic, martial law in Ukraine, and others. Conclusions. The scientific novelty of the article is that it compares event trends of different years, identifies their advantages and disadvantages, and suggests prospects for further research. The conclusions drawn from the study focus on the diversity of trends and their formation, depending on external circumstances. The ideas proposed in the article will allow adapting global trends to domestic realities. It will help to increase the competitiveness of Ukrainian events both in the local and large-scale international markets.